Kinerja TV Publik: Analisis Isi Berita TVRI tentang Kampanye Pemilu Legislatif 2004 - Darmanto, A. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2004)
Given its official status as a public television, TVRI has not been able to put the impartial principle in broadcasting it news on general election. Factionally, the channel has been in favour to the rulling party and spatially, it serves Java region particularly Jakarta better than the rest of the country.